Regional innovation strategy as a policy instrument - Hudec, Oto (Észak-magyarországi Stratégiai Füzetek, 2007)
The historical, cultural, political and economical disparateness of eventual trans-boundary regions makes the learning process of building regional identity, single economic space rather complex. The creation of a cross-border regional innovation strategy can play important role in enhancement of the interregional and international cooperation and competitiveness. This is particularly true on the parallel background of regionalisation of innovation systems in the most European countries. Also, former ideas of a success of innovation policies in developed countries and/or regions can be applied in lagging regions as well, taking into account special conditions and to fashion the regional strategy according to the character of the region of consideration. Cross-border regional innovation strategy as a tool for developing cross-border economic relations has a good chance to utilise regional integration effects in conditions of noncooperating border regions and in enhancement of the interregional and international cooperation and competitiveness.